Disease surveillance of the amphibian chytrid fungus Batrachochytrium dendrobatidis in Papua New Guinea. Issue 9 (17th August 2020) - Bower, Deborah S.; Jennings, Charlotte K.; Webb, Rebecca J.; Amepou, Yolarnie; Schwarzkopf, Lin; Berger, Lee; Alford, Ross A.; Georges, Arthur; McKnight, Donald T.; Carr, Leah; Nason, Dillian; Clulow, Simon
Abstract: Emerging infectious diseases threaten the persistence of biodiversity globally. The amphibian chytrid fungus, Batrachochytrium dendrobatidis, is one of the most widespread and damaging pathogens to biodiversity. New Guinea hosts 6% of the world's frogs and is the largest landmass where B. dendrobatidis remains undetected despite being largely climatically suitable for its persistence. We surveyed for B. dendrobatidis in Papua New Guinea, by swabbing live frogs in the Gulf Province and Eastern Highlands Province and by examining museum specimens from a range of sites and elevations. Here, we show that over a large geographical range, all 442 samples were negative for B. dendrobatidis . The spread of B. dendrobatidis to Papua New Guinea may have been thus far prevented by the remoteness of New Guinea and the hotter climate in its lowlands, which surrounds a more climatically suitable zone for B. dendrobatidis in the highlands. Alternatively, B. dendrobatidis may be present in isolated patches or at low levels and remain undetected, to date. Papua New Guinea remains at risk and would benefit from a national disease surveillance program for chytrid fungi and pre‐emptive actions, designed to reduce the risk of pathogen transmission. Measures should include improved biosecurity protocols for trade and travel and continued disease surveillance in areas of probable entry and spread. Abstract :